ANALISIS KESULITAN SISWA DALAM MEMAHAMI SOAL CERITA MATEMATIKA PADA MATERI PELUANG - Iis Budiyanti Putridayani; Siti Chotimah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study has the aim of analyzing students' difficulties in understanding the story questions on the opportunity material. This type of research is descriptive research with a qualitative approach. The subjects of this research were 22 students of class XI SMAN 1 Cipeundeuy. Retrieval of data in this study was to use the results of the student's answer test based on the instrument of probability in the form of a description consisting of five items. The data processing in this research is by using the percentage formula to see the picture. From this research, it can also be concluded that students do not master the concept of opportunity so that students have difficulty solving the opportunity material story questions.